Management of recurrent corneal erosions: A stepwise approach (Canadian Eye Care Today, 2023)
Recurrent corneal erosions syndrome (RCES) is a common disorder characterized by recurring episodes of corneal epithelial breakdown. Symptoms include pain, tearing or redness typically worse upon awakening or overnight during rapid eye movements (REM) sleep. Severe episodes can last for days, leading to epithelial defects and corneal scarring. Recurrences can be frequent and debilitating for patients. The aim of this review is to summarize the current medical and surgical methods available to treat RCES.